A RARE CASE OF NONFUNCTIONING APPENDICEAL NEUROENDOCRINE TUMOUR (ANET) WITH BASE INVOLVEMENT NEEDING HEMICOLECTOMY - Mokti, Abdullah Shamshir Abd; Azwan, Raja Nurazni Raja (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Appendiceal neuroendocrine tumour (ANET) is the commonest appendiceal tumour found in 0.2–0.7% of surgical resections for suspected appendicitis. Peak incidence is at age 40-50 years with slight female preponderance. If diagnosed at a lower stage, survival is extremely good; local disease has 5- year survival rate (5-YSR) of between 95–100% and regional disease has between 85–100% 5-YSR. However, cases with distant metastasis present with relatively poor survival figures with 5-YSR less than 25%. We report a rare case of a patient with ANET with involvement of the base of the appendix needing further anatomical and functional imaging and right hemicolectomy. CASE A 45-year-old female presented with acute right iliac fossa pain of less than 24 hours of duration with vomiting which led to a diagnosis of presumed appendicitis. She underwent laparoscopic appendectomy and intraoperatively was found to have adhesions with the abdominal wall and the appendix was only mildly inflamed. Histologic examination confirmed neuroendocrine tumour of the appendix with base of appendix involvement. Contrastenhanced CT showed suspicious nodule in both upper and lower lobes of the lungs. Gallium dotatate PET Scan showed no dotatate-avid lesions in the bowels, lymph nodes and lung metastases. Due to involvement of appendiceal base, a decision of hemicolectomy was made. Histopathology showed no evidence of tumour involvement in bowel. CONCLUSION Although ANETs are usually benign, non-functional and have good prognosis, it is important to identify features needing further anatomical and functional imaging which would determine whether right hemicolectomy is needed to prevent metastases or recurrence.